2022
DOI: 10.3389/fcimb.2022.979641
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of a chimpanzee adenovirus vector expressing a pre-fusion spike (BV-AdCoV-1) protects golden Syrian hamsters against SARS-CoV-2 infection

Abstract: We evaluated the immunogenicity and protective ability of a chimpanzee replication-deficient adenovirus vectored COVID-19 vaccine (BV-AdCoV-1) expressing a stabilized pre-fusion SARS-CoV-2 spike glycoprotein in golden Syrian hamsters. Intranasal administration of BV-AdCoV-1 elicited strong humoral and cellular immunity in the animals. Furthermore, vaccination prevented weight loss, reduced SARS-CoV-2 infectious virus titers in the lungs as well as lung pathology and provided protection against SARS-CoV-2 live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Strikingly, neutralization titers against BA.2 were non-existent after a single dose in hamsters and only detectable in four out of 20 animals after a booster dose. This contrasts both adenovirus and modified vaccinia Ankara (MVA) vaccines encoding the Wuhan spike in its wildtype or prefusion conformation (two proline substitution) where robust cross-reactive serum neutralizing antibodies are observed [62][63][64][65][66][67] . Induced antibodies exhibited varied binding abilities to different VOCs, as observed with the antibodies resultant of NDV-PFS vaccination 62,63,66,67 .…”
Section: Discussionmentioning
confidence: 94%
“…Strikingly, neutralization titers against BA.2 were non-existent after a single dose in hamsters and only detectable in four out of 20 animals after a booster dose. This contrasts both adenovirus and modified vaccinia Ankara (MVA) vaccines encoding the Wuhan spike in its wildtype or prefusion conformation (two proline substitution) where robust cross-reactive serum neutralizing antibodies are observed [62][63][64][65][66][67] . Induced antibodies exhibited varied binding abilities to different VOCs, as observed with the antibodies resultant of NDV-PFS vaccination 62,63,66,67 .…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that the intranasal administration of BV-AdCoV-1 induced strong humoral and cellular protective immunity in golden hamsters [ 25 ]. We turned to the non–human primate model to further compare the respective efficiencies of intranasal administration (IN) and aerosol inhalation (IH).…”
Section: Resultsmentioning
confidence: 99%
“…The prime–boost schedules of COVID-19 vaccines have unambiguously demonstrated their safety, clinical effectiveness, and efficacy [ 25 ]. However, recent reports have consistently highlighted that immunity begins to decline 6–8 months after two vaccine doses [ 1 ], exposing vaccinees to re–infection or breakthrough infections, in particular by emerging SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main route of infection by SARS-CoV-2 is through the upper respiratory tract, and a vaccine with a protective effect at the site of infection is desired. In contrast to intramuscular vaccination, mucosal immunization is a non-invasive procedure that induces a strong and long-lasting secretory immunoglobulin A (IgA) response and plays an important role in defense against viral infection of the upper respiratory tract (1)(2)(3). Therefore, it is important to study mucosal immunity, especially nasal immunity, which has been shown to play an important role in IgA production, mainly in nasal-associated lymphoid tissue (NALT) and Waldeyer's tonsillar ring (4)(5)(6), which appears to be functionally equivalent to NALT in rodents (7).…”
Section: Introductionmentioning
confidence: 99%